Implications and strategies of safety management in high rise building construction to contractor / Akalili Husna Kamall Rudin and Siti Nurhayati Hussin - Kamall Rudin, Akalili Husna; Hussin, Siti Nurhayati (2018)
High rise building construction sites are one of the most dangerous places due to possible accidents occurring at the site especially for workers as machineries could fall from high places. Contractors whom successfully are able to manage the safety procedures at sites could significantly decrease the amount of accidents to occur. This paper will provide abundant information on the implications of safety management upon contractors a thigh rise building construction sites. The objectives of this research are to investigate on the implications of safety management at construction sites as well as to determine effective strategies in reducing problems of safety practices and also to investigate on implications of safety management towards building construction works. A qualitative method was used as the methodology for this research in which questionnaires are given to safety officers of the contractor's company who are currently developing high rise buildings in Kuala Lumpur. Results of the research show that safety management should be implemented at sites in order to reduce the number of accidents. Therefore, the study found out that the best strategy in avoiding accidents to occur at construction sites is that contractors should always maintain their image among the workers as well as to constantly award and show respect towards them. As a conclusion, it is imperative that contractors manage safety procedures at construction sites in order to avoid accidents to occur which indirectly can decrease the amount of financial spent on accidents. Thus, when no accidents occur at construction sites, this will also be good for the image and reputation of the contractor.